Experimental and Numerical Study of Crack Effect on Frequency of Simple Supported Beam - Ali M. H.Yusif Al-Hajjar (Al-Khwarizmi College of Engineering – University of Baghdad, 2012)
In this research the natural frequency of a cracked simple supported beam (the crack is in many places and in different depths) is investigated analytically, experimentally and numerically by ANSYS program, and the results are compared. The beam is made of iron with dimensions of L*W*H= (0.84*0.02* 0.02m), and density = 7680kg/m3, E=200Gpa. A comparison made between analytical results from ANSYS with experimental results, where the biggest error percentage is about (7.2 %) in crack position (42 cm) and (6 mm) depth. Between Rayleigh method with experimental results the biggest error percentage is about (6.4 %) for the same crack position and depth. From the error percentages it could be concluded that the Rayleigh method gives close results to experimental than ANSYS. Also it is found that the frequency of beam when the crack is in the middle position is less than the frequency with crack near the end position.